Hydro‐carbon material design in a capacitively coupled radio‐frequency discharge. Issue 3 (14th December 2017) - Mitic, Slobodan; Coussan, Stéphane; Martin, Céline; Couëdel, Lénaïc
Abstract : The synthesis and the growth of carbonaceous microparticles is observed in a capacitively coupled radio‐frequency discharge in controlled adamantane‐acetylene gas mixtures. The plasma is characterized by optical emission spectroscopy and mass spectroscopy while the produced particles were analyzed ex situ using Fourier‐Transform infrared absorption spectroscopy. It is revealed that the adamantane to acetylene ratio controlled the particle material properties, in particular the type of chemical bonds between the constituting polymers. Systematic and consistent changes in plasma parameters when changing the adamantane to acetylene ratio are also reported and are correlated to the evolution of particle material properties. Abstract : Plasma from different acetylene to adamantane ratio is used for synthesis of micron size particles with different material properties. Besides the obvious changes in particle color, detailed particle analysis shows that systematic changes in type of chemical bonds between constituting polymers can be correlated to changes in plasma composition. Adamantane is identified as a source of large diamond‐like cage structures integrated into the particle by bonding hydrocarbon fragments.